Temporal trends of ischemic stroke attributable to diet high in sodium in China from the global burden of disease study 2021 - Cui, Jiaming; Xu, Zhiwei; Dai, Yang; Wang, Qi; Hou, Zhihui; Zhang, Yongchen; Jia, Hongling (Frontiers in Nutrition, 2025)
BackgroundIschemic stroke is a significant global health burden, with high sodium intake recognized as a key risk factor. This study aimed to assess the disease burden of ischemic stroke attributable to diet high in sodium in China from 1990 to 2021. Additionally, we analyzed the influence of age, period, and cohort effects on the trends in ischemic stroke burden and projected the disease burden from 2022 to 2036.MethodsData from the Global Burden of Disease Study 2021 (GBD 2021) were used to analyze the ischemic stroke burden among high-risk populations in China. Annual average percent change (AAPC) was calculated using Joinpoint regression models to evaluate trends in ischemic stroke burden from 1990 to 2021. Age-period-cohort models were employed to estimate the independent effects of age, period, and cohort on the ischemic stroke burden, and to project the burden from 2022 to 2036 using Bayesian age-period-cohort models.ResultsFrom 1990 to 2021, ischemic stroke mortality attributable to diet high in sodium in China showed a continuous increase, while the age-standardized mortality and disability-adjusted life years (DALYs) significantly declined. In the age-period-cohort analysis, the age effect on ischemic stroke burden increased steadily over the study period. Period effects revealed an initial decline in the relative risk (RR) of ischemic stroke mortality and DALY rates, followed by an increase in cohorts born before 2004–2009, and a gradual decline in cohorts born after that period. Cohort effects demonstrated a continuous decline in the relative risk of ischemic stroke mortality and DALY rates from 1990 to 2021.ConclusionThis study found that ischemic stroke attributable to a diet high in sodium in China fluctuated from 1990 to 2021, with a declining trend observed in recent years. Projections indicate that this downward trend will continue. Age and birth period are key factors influencing the disease burden, with older adults and men being particularly affected. Future policy efforts should focus on enhancing health management in high-risk populations to further reduce the burden of ischemic stroke linked to high sodium intake.